2008
DOI: 10.3390/ijerph5030165
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Analysis of Road Traffic Noise in Asansol: An Industrial Town of Eastern India

Abstract: The objectives of the study were to monitor and assess the road traffic noise in its spatial-temporal aspect in an urban area. The paper discusses the observations, results and their interpretation based on the study. Noise recordings from site, collected from April 2006 to March 2006, were used for statistical analysis and generation of various noise indices. Noise maps were also created for impact analysis and formulation of Noise Risk Zones. Mean Ldn value ranged between 55.1 and 87.3 dB (A). Day time Leq l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 3 publications
3
35
0
1
Order By: Relevance
“…Asansol, an urban-industrial city situated in West Bengal state of eastern India, with an area of 127 km 2 and a population density of 3737/km 2 has witnessed a sharp growth in vehicular population in the last five years, ensuing a significant, unrestrained noise pollution across the area as reported in previous works (Banerjee and Chakraborty, 2005;Banerjee et al, 2008a). The impact identification and quantification due to such exposure to road traffic noise has been done in such preceding works and it has been observed that such noise levels in the area are much above the prescribed limits (Banerjee et al, 2008b).…”
Section: Study Areamentioning
confidence: 73%
“…Asansol, an urban-industrial city situated in West Bengal state of eastern India, with an area of 127 km 2 and a population density of 3737/km 2 has witnessed a sharp growth in vehicular population in the last five years, ensuing a significant, unrestrained noise pollution across the area as reported in previous works (Banerjee and Chakraborty, 2005;Banerjee et al, 2008a). The impact identification and quantification due to such exposure to road traffic noise has been done in such preceding works and it has been observed that such noise levels in the area are much above the prescribed limits (Banerjee et al, 2008b).…”
Section: Study Areamentioning
confidence: 73%
“…An EF of > 1 indicates that the traffic noise level was in excess of the daytime commercial area standard prescribed by the CPCB in both seasons. Traffic noise levels greater than the prescribed standard in Indian cities has been reported by a number of researchers (24)(25)(26)(27). The average EF for PM 2.5 concentration (EF-PM 2.5 ) was 7.34 ± 1.74 post-monsoon and 3.35 ± 0.89 pre-monsoon.…”
Section: Ef Of Traffic Noise and Concentrations Of Air Pollutantsmentioning
confidence: 88%
“…The comparison of ambient noise levels observed in 2015 with those observed in 2011 for the 35 stations revealed that, for some sites like Indira Nagar, PGI Hospital of Lucknow city; Kasba Gole park, Patauli and New Market site of Kolkata city; ASHP and MPCB headquarters of Mumbai city; Abids and Jeedimetla site of Hyderabad city; Eye hospital, Perambur, T. Nagar and Triplicane sites in Chennai city registered a higher increment (5 dB(A)) in ambient noise levels. This may be primarily due to the substantial growth of new vehicles, low turnover of old vehicles, inadequate road network and urbanization [19][20][21][22][23][24] . Table 5 shows the frequency distribution of L day and L night ; L dn and L Aeq,24 h in dB(A) for seven major cities (70 sites) in 2015.…”
Section: Overall Noise Scenariomentioning
confidence: 99%